2016
DOI: 10.1142/s0219843616500092
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study for Postural Synergy Synthesis Using Linear and Nonlinear Methods

Abstract: Human controls dozens of muscles for different hand postures in a coordinated manner. Such coordination is referred to as a postural synergy. Postural synergy has enabled an anthropomorphic robotic hand with many actuators to be applied as a prosthetic hand and controlled by two to three channels of biological signals. Principle component analysis (PCA) of the hand postures has become a popular way to extract the postural synergies. However, relatively big errors are often produced while the hand postures are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The methods presented until now in this section were deterministic. In Romero et al (2013); Xu et al (2016), the Gaussian Process Latent Variable Model (GPLVM) (Lawrence, 2003), which is a non linear probabilistic model, was used to learn a grasp manifold from a dataset of recorded grasp postures. They showed that this model has lower reconstruction error when compared with the PCA.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…The methods presented until now in this section were deterministic. In Romero et al (2013); Xu et al (2016), the Gaussian Process Latent Variable Model (GPLVM) (Lawrence, 2003), which is a non linear probabilistic model, was used to learn a grasp manifold from a dataset of recorded grasp postures. They showed that this model has lower reconstruction error when compared with the PCA.…”
Section: Related Workmentioning
confidence: 99%
“…Following works (Romero et al, 2013;Xu et al, 2016), have improved the reconstruction error of the grasp postures, when compared with PCA, by using a non-linear latent variable model based on Gaussian processes (GPLVM). Auto-Encoder (AE) models, which is a non-linear, deterministic dimensionality reduction method, based on neural networks, have also been shown to improve the performance in terms of reconstruction and are able to encode additional information such as the object size (Starke et al, 2018(Starke et al, , 2020.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [53] a Gaussian Process Latent Variable Model (GPLVM) is used to model the subspace of human hand motions, demonstrating better performance in reconstructing spatial and temporal grasping actions with respect to PCA and Isomap. A comparison between linear and nonlinear synergies can be found in [54].…”
Section: Dimensionality Reduction and Postural Synergiesmentioning
confidence: 99%